Behaviour of slender reinforced concrete columns - Khoo, Wen Zhong. (2010)
Columns are important structural members and slender reinforced concrete columns are both aesthetically and economically appealing. Because of this, it is being used with increasing regularity in modern structures today. Technology for producing and placing the slender reinforced concrete columns are also improving rapidly to keep up with the increasing demand. However, the behaviour of columns have been researched for many years but relatively few tests have been carried out on slender reinforced concrete columns, especially for biaxial loaded columns. The objective of this project is to study the effects that different parameters such as concrete strength, steel ratio, eccentricity ratio, slenderness ratio, steel yield strength and long-term sustained loading have on the behaviour slender reinforced concrete columns. The report will also contain information about failure modes, failure loads, deflections and strains. This will be done by first doing a literature review about the history of slender reinforced concrete columns. This will be followed by a thorough analysis of the effects that different parameters have on slender reinforced concrete columns. As this final year project will not involve the conducting of any experiments on slender reinforced concrete columns, the author will analyze the experimental data done by Andreas Dracos [1982], Daud F. Jabaji [1974], Foo Seng Heng [1993 & 1996], Kong Sia Keong [1996], Chan Jee Khin [1996] and David Schofield [1983] and do a discussion and conclusion based on their results. Recommendations will also be given after a discussion and conclusion is done.